Identification of compounds in heavy fuel oil that are chronically toxic to rainbow trout embryos by effects‐driven chemical fractionation. (18th February 2014) - Adams, Julie; Bornstein, Jason M.; Munno, Keenan; Hollebone, Bruce; King, Thomas; Brown, R. Stephen; Hodson, Peter V.
Abstract The present study isolated and identified compounds in heavy fuel oil 7102 (HFO 7102) that are bioavailable and chronically toxic to rainbow trout embryos (Oncorhynchus mykiss). An effects‐driven chemical fractionation combined the chemical separation of oil with toxicity testing and chemical analyses of each fraction to identify the major classes of compounds associated with embryo toxicity. Toxicity was assessed with 2 exposure methods, a high‐energy chemical dispersion of oil in water, which included oil droplets in test solutions, and water accommodated fractions which were produced by oiled gravel desorption columns, and which did not contain visible oil droplets. Fractions of HFO with high concentrations of naphthalenes, alkanes, asphaltenes, and resins were nontoxic to embryos over the range of concentrations tested. In contrast, fractions enriched with 3‐ to 4‐ringed alkyl polycyclic aromatic hydrocarbons (PAHs) were embryotoxic, consistent with published studies of crude oils and individual alkyl PAHs. The rank order of fraction toxicity did not vary between the exposure methods and was consistent with their PAH content; fractions with higher–molecular weight alkyl PAHs were the most toxic. Exposure of juvenile trout to most fractions of HFO induced higher activities of cytochrome P450 enzymes, with a rank order of potency that varied with exposure method and differed somewhat from that of embryotoxicity. Induction reflected the bioavailability of PAHs but did not accurately predict embryotoxicity. Environ Toxicol Chem 2014;33:825–835. © 2013 SETAC